2012
DOI: 10.4274/tnd.34603
|View full text |Cite
|
Sign up to set email alerts
|

Fahr Syndrome Due To Idiopathic Hypoparathyroidism

Abstract: Fahr Sendromu bazal ganglia, sentrum semiovale ve serebellumda kalsifikasyona yol açan, klinikte parkinsonizm ve bilişsel yıkım bulgularıyla karakterize bir hastalık olup hipoparatiroidizm ve psödohipoparatiroidizm gibi metabolik sorunlara bağlı olarak da görülebilir (1,2). Tipik radyolojik bulguları tanıya yaklaşımda yol göstericidir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In terms of the dark side of late career participation, it is shown that late career participation can decrease non–job-related physical activity that is performed outside of work setting and is irrelevant to the achievement of job goals (eg, active travel in the commuting, entertainment purpose, exercise purpose). Non–job-related (or leisure purpose) physical activity can alleviate negative emotions and negative psychological outcomes of retirement-aged workers, 13 due to the enhancement of social activity participation and access to social support, 14 the decrease in loneliness, 15 the improvement in subjective well-being and life satisfaction, 15 and the increase in ones’ self-concept and a sense of control and dominance 16 . It is suggested that non–job-related physical activity can play an effective role in depression treatment for retirement-aged workers 17 .…”
mentioning
confidence: 99%
“…In terms of the dark side of late career participation, it is shown that late career participation can decrease non–job-related physical activity that is performed outside of work setting and is irrelevant to the achievement of job goals (eg, active travel in the commuting, entertainment purpose, exercise purpose). Non–job-related (or leisure purpose) physical activity can alleviate negative emotions and negative psychological outcomes of retirement-aged workers, 13 due to the enhancement of social activity participation and access to social support, 14 the decrease in loneliness, 15 the improvement in subjective well-being and life satisfaction, 15 and the increase in ones’ self-concept and a sense of control and dominance 16 . It is suggested that non–job-related physical activity can play an effective role in depression treatment for retirement-aged workers 17 .…”
mentioning
confidence: 99%